Health care utilization and mortality for people with epilepsy during COVID‐19: A population study - Huw Strafford (Epilepsia, 2024)
Objective: This study was undertaken to characterize changes in health care utilization and mortality for people with epilepsy (PWE) during the COVID-19 pandemic. Methods: We performed a retrospective study using linked, individual-level, population-scale anonymized health data from the Secure Anonymised Information Linkage databank. We identified PWE living in Wales during the study “pandemic period” (January 1, 2020–June 30, 2021) and during a “prepandemic” period (January 1, 2016–December 31, 2019). We compared prepandemic health care utilization, status epilepticus, and mortality rates with corresponding pandemic rates for PWE and people without epilepsy (PWOE). We performed subgroup analyses on children (<18 years old), older people (>65 years old), those with intellectual disability, and those living in the most deprived areas. We used Poisson models to calculate adjusted rate ratios (RRs). Results: We identified 27 279 PWE who had significantly higher rates of hospital (50.3 visits/1000 patient months), emergency department (55.7), and outpatient attendance (172.4) when compared to PWOE (corresponding figures: 25.7, 25.2, and 87.0) in the prepandemic period. Hospital and epilepsy-related hospital admissions, and emergency department and outpatient attendances all reduced significantly for PWE (and all subgroups) during the pandemic period. RRs [95% confidence intervals (CIs)] for pandemic versus prepandemic periods were .70 [.69–.72], .77 [.73–.81], .78 [.77–.79], and .80 [.79–.81]. The corresponding rates also reduced for PWOE. New epilepsy diagnosis rates decreased during the pandemic compared with the prepandemic period (2.3/100 000/month cf. 3.1/100 000/month, RR = .73, 95% CI = .68–.78). Both all-cause deaths and deaths with epilepsy recorded on the death certificate increased for PWE during the pandemic (RR = 1.07, 95% CI = .997–1.145 and RR = 2.44, 95% CI = 2.12–2.81). When removing COVID deaths, RRs were .88 (95% CI = .81–.95) and 1.29 (95% CI = 1.08–1.53). Status epilepticus rates did not change significantly during the pandemic (RR = .95, 95% CI = .78–1.15). Significance: All-cause non-COVID deaths did not increase but non-COVID deaths associated with epilepsy did increase for PWE during the COVID-19 pandemic. The longer term effects of the decrease in new epilepsy diagnoses and health care utilization and increase in deaths associated with epilepsy need further research. Key Points: People with epilepsy have increased rates of hospital, emergency department, and outpatient attendance when compared to people without epilepsy.These rates (and rates of new epilepsy diagnoses) reduced significantly during our pandemic study period (January 1, 2020–June 30, 2021).Rates of status epilepticus did not change during the pandemic period.All-cause non-COVID deaths did not increase for people with epilepsy.There was a small increase in non-COVID deaths with epilepsy listed as a cause for people with epilepsy.